Literary Discourses of Industrial Cities. On the Examples of the Dąbrowa Basin - Tomczok, Paweł (Porównania, 2024)
This article discusses the literary discourses of industrial cities from industrialization in the nineteenth century to deindustrialization. At the beginning of this article, the similarity of literary and sociological images of industrial cities was emphasized, thus creating a negative image of these places. Particular attention was paid to the literary works, memories, and sociology of the Dąbrowa Basin. This industrial region was the subject of interest to many Polish writers at the end of the nineteenth century. This article confronts the negative discourse of industrial cities from the perspective of residents who-under challenging conditions-created various lifestyles and support networks, thanks to which it was possible to organize life in industrial slums. In the post-war period, the negative discourse about industrial cities served as a critical argument for demolishing old districts and building in their place concrete housing estates, which are still the spatial dominant of the Dąbrowa Basin region.